2022
DOI: 10.1021/acs.jpcc.2c05422
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Time Dynamics of Hydrogen Spillover from a Single Atom Platinum Active Site to the Cu(111) Host Surface

Abstract: Dynamics of the dissociative chemisorption of H2 (D2) and the subsequent H* (D*) diffusion on the Pt doped Cu(111) surface are investigated using both quasi-classical trajectory (QCT) and ring polymer molecular dynamics (RPMD) approaches. The classical dynamics is also studied with electronic friction to simulate the nonadiabatic interaction with surface electron–hole pairs. These dynamics calculations were made possible by a high-dimensional potential energy surface, machine learned from density functional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 70 publications
(152 reference statements)
3
18
0
Order By: Relevance
“…On the other hand, the one at the fcc site at the transition state is more likely to travel, across one or two Ru surface lattice units (2.7 Å). This behavior, namely, only one of the two atomic adsorbates is involved in diffusion, is quite similar to the hot H dynamics after the dissociation of H 2 . ,, In Figure , the N–N separation averaged over all of the dissociated trajectories is shown as a function of time. Here, the N–N distance is computed directly from their Cartesian coordinates.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…On the other hand, the one at the fcc site at the transition state is more likely to travel, across one or two Ru surface lattice units (2.7 Å). This behavior, namely, only one of the two atomic adsorbates is involved in diffusion, is quite similar to the hot H dynamics after the dissociation of H 2 . ,, In Figure , the N–N separation averaged over all of the dissociated trajectories is shown as a function of time. Here, the N–N distance is computed directly from their Cartesian coordinates.…”
Section: Resultssupporting
confidence: 52%
“…Indeed, our recent work on H spillover had shown that interactions with substrate EHPs significantly slow down the diffusion of adsorbed H atoms, leading to smaller diffusion coefficients than those obtained via adiabatic simulations. 39,40 In addition, previous studies on N diffusion on metal surfaces have demonstrated that the nonadiabatic friction is typically minor. 27 If the electronic friction were to be included in our simulation, it can be expected that the final N−N separation would be even smaller.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an early work, Suleimanov applied the RPMD rate theory to calculate diffusion constants of hydrogen on Ni(100) with an embedded atom method interatomic potential. 51 More recently, non-equilibrium RPMD simulations for gas-surface scattering have been carried out to calculate dissociative sticking probabilities [52][53][54][55] and diffusion constants of hydrogen on a single-atom catalytic surface 56 .…”
Section: Introductionmentioning
confidence: 99%